UPAYA MENGATASI BUTA AKSARA AL-QUR’AN DI KEC. TANETE RIATTANG TIMUR KABUPATEN BONE - Andi Rahmat Abidin; Saddam Husein (IAIN Ambon, 2022)
Abstract: This study uses qualitative research methods using three approaches, namely: pedagogical approach, psychological approach and sociological approach. The data in this study were obtained through primary data and secondary data, namely observations, interviews and documentation. The research instrument is in the form of observation guidelines, interview guidelines and documentation. The results of this study indicate that the form of government and community collaboration in efforts to eradicate illiteracy in the Qur'an in Tanete Riattang Timur District, Bone Regency has really materialized well. The forms of government and community cooperation are: Government and community cooperation in the form of energy donations, government and community cooperation in providing ideas, government and community cooperation in material donations and government and community cooperation in providing moral support. Government and community collaboration in efforts to eradicate al-Quran illiteracy in Tanete Riattang Timur District, Bone Regency, namely the existence of an approach with learning residents, fun learning, activities outside of learning and motivating residents to learn the Koran. There are three opportunities in eradicating illiteracy in the Qur'an, namely the existence of schools, facilities and infrastructure and management. Government and community collaboration in efforts to eradicate illiteracy in the Qur'an has many benefits, including: Establishment of TK/TPA, construction of mosques and formation of ta'lim councils. With this collaboration, the residents of the Tanete Riattang Subdistrict are increasingly pious and have faith in God Almighty, have noble character, are independent, have good personalities, and are physically and mentally healthy. Keywords: Government and Community Cooperation, Al-Quran Illiteracy EradicationAbstrak: Penelitian ini bertujuan untuk mengetahui upaya pengentasan buta aksara Al-Qur’an di kecamatan tanete riattang timur kabupaten bone. Penelitian ini menggunakan metode penelitian kualitatif dengan menggunakan tiga pendekatan yaitu: Pendekatan paedagogis, pendekatan psikologis dan pendekatan sosiologis. Data dalam penelitian ini diperoleh melalui data primer dan data sekunder yaitu obsevasi, wawancara. Instrumen penelitian ini berupa pedoman observasi, pedoman wawancara dan dokumentasi. Hasil penelitian ini menunjukkan bentuk kerjasama pemerintah dan masyarakat dalam upaya pengentasan buta aksara Al-Qur’an di Kecamatan Tanete Riattang Timur Kabupaten Bone benar-benar terwujud dengan baik. Adapun bentuk kerjasama pemerintah dan masyarakat yaitu: Kerjasama pemerintah dan masyarakat dalam bentuk sumbangan tenaga, kerjasama pemerintah dan masyarakat dalam memberikan buah pikiran, kerjasama pemerintah dan masyarakat dalam sumbangan material dan kerja sama pemerintah dan masyarakat dalam memberikan dukungan moral. Kerjasama pemerintah dan masyarakat dalam upaya pengentasan buta aksara al-Quran di Kecamatan Tanete Riattang Timur Kabupaten Bone yaitu adanya pendekatan dengan warga belajar, pembelajaran yang menyenangkan, adanya kegiatan di luar pembelajaran dan memotivasi warga belajar al-Qur’an. Terdapat tiga peluang dalam pengentasan buta aksara Al-Qur’an yaitu adanya sekolah, sarana dan prasarana dan manajemen. Kerjasama pemerintah dan masyarakat dalam upaya pengentasan buta aksara Al-Qur’an memiliki banyak manfaat di antaranya: Pembentukan TK/TPA, pembangunan masjid dan pembentukan majlis ta’lim. Dengan adanya Kerjasama ini, menjadikan warga masyarakat Kecamatan Tanete Riattang semakin bertakwa dan beriman kepada Tuhan yang Maha Esa, berbudi pekerti luhur, mandiri, berkepribadian, serta sehat jasmani dan rohani. Kata Kunci : Kerjasama Pemerintah Dan Masyarakat, Pengentasan Buta Aksara Al-Qur’an